Diversity of soil fertility management options in maize-based farming systems in northern Benin: A quantitative survey - Tovihoudji, Pierre G.; Akpo, Firmin I.; Tassou Zakari, F.; Ollabodé, Nouroudine; Yegbemey, Rosaine N.; Yabi, Jacob A. (Frontiers in Environmental Science, 2023)
Several practices are used for the management and sustainable maintenance of soil fertility in maize production systems in northern Benin. This article aims to identify practical and characterize. The study was conducted in the municipalities of Malanville, Banikoara and Bembèrèkè. A total of 262 maize farmers were sampled randomly and were interviewed. Descriptive statistical tests (chi-square, ANOVA, distribution of means and frequencies, etc.) were used for this purpose. SPSS 21 software was used to analyze the data. The characteristics of maize-based cropping systems are the maize-legume intercropping, maize-cotton rotation, intake of mineral and organic fertilizers, and the combined use (organic + mineral) and .23,6% 58.4% of producers have consistently used mineral fertilizer respectively over the last 5 and 10 years. The mean dose of NPK used by food producers is 62.5 (± 67.1) kg/ha applied 18 (±3) days after sowing. The average amount of cotton NPK is 123.9 (± 43.3) kg/ha applied at 22 (±9) days after sowing. As for urea, it is applied 41 (± 10) days after sowing with an average amount of 61.1 (±23.9) kg/ha. The mixture (cotton NPK + Urea) is used at a dose of 153.27 (± 60) kg/ha applied at 38 (± 11) days after sowing. Most producers spread the fertilizer around the plants without covering with soil layer. 28.2% of respondents use farmyard manure and cattle penning in their farm system. Most growers use manure from their own livestock. Penning cattle is done by a minority of producers. Strengthening and technical assistance to producers on the production of organic fertilizers and plant sufficient manure storage facilities prove necessary to resolve the problems associated with the shortage or unavailability of fertilizer on the Beninese market.